Gender Analysis From a Review of Middle School Students' Attitudes and Self-efficacy - Zurweni, Zurweni; Kurniawan, Dwi Agus; Rivani, Putri Ayu; Perdana, Rahmat (Jurnal Pendidikan Indonesia, 2022)
Education is important to increase human resources so that in education one of them needs attitude and self-efficacy in students. This study aims to analyze the differences and the relationship between attitudes and self-efficacy of science students. This study uses quantitative methods with associative and comparative types. The instrument used was a questionnaire linkers scale consisting of 5 categories. The numbers of respondents in this study were 160 students of two classes namely: class VIIA and VIIB. Differential statistical test is carried out by testing assumptions and testing hypotheses. Based on the results of the study, the attitude and self-efficacy t-test of class VII A and VII B students had significant differences. This was evidenced by the value of sig (2-tailed) < 0.05. And the correlation test scores of female students and male students of grades VII A and VIIB have a significant relationship, this is evidenced by the value of sig (2-tailed) which is <0.05. With the results obtained that there is a comparison between female students and male students on each indicator. Students' attitudes and self-efficacy towards science learning are categorized as good enough for both female and male students. The results of the tests that have been carried out in this study also show that there are differences and relationships between attitudes and self-efficacy on the gender of students. However, most of the students' attitudes have a category that tends to be quite good.